Analisis Evaluasi Kesesuaian Lahan Beberapa Komoditas Pertanian Tanaman Pangan di Pulau Nusalaut Kabupaten Maluku Tengah - Semuel Laimeheriwa; Robby G. Risamasu; Reni Tomasoa; Edison Jambormias (Jurnal Indonesia Sosial Sains, 2022)
This research was conducted on Nusalaut Island, Central Maluku Regency, aiming to determine the land suitability class of several food crop commodities. Data collection and analysis methods include: (1) analysis of thematic maps, (2) preparation of Land Unit Maps (PSL), (3) field checking using the field survey method, which uses independent survey techniques; (4) observation of land characteristics and quality in each land unit, and (5) analysis of land characteristics and quality in each land unit. The follow-up analysis is in the form of: (1) determining the level of land suitability and (2) producing a map of land suitability classes for food crop commodities on the island of Nusalaut. The results of the assessment of land suitability class on food crops cassava, sweet potato, and corn included in the category of marginally suitable class (S3) with limiting factors of water availability (wa), rooting media (rc), slope (eh) and unsuitable class (N). Cassava plantations had a marginally suitable class (S3) with a limiting factor (wa, rc) of 1452.4 ha or 66.51% and for an unsuitable class (N) of 731.52 ha or 33.50%. Sweet potato plants have a marginally suitable class (S3) with a limiting factor (wa, rc, eh) covering an area of ​​1452.38 ha or 66.5% and for an unsuitable class (N) an area of ​​731.52 ha or 33.50%. Corn plants have a marginal suitable class (S3) with a limiting factor (wa, rc) covering an area of ​​1452.38 ha or 66.5% and for an unsuitable class (N) an area of ​​731.52 ha or 33.50%.